2012
DOI: 10.1371/journal.pone.0051804
|View full text |Cite|
|
Sign up to set email alerts
|

Trypanosoma cruzi: Role of δ-Amastin on Extracellular Amastigote Cell Invasion and Differentiation

Abstract: Trypanosoma cruzi is a protozoan parasite that comprises different phylogenetic groups and is the causative agent of Chagas’ disease. Different T. cruzi strains present differences in infectivity in in vitro and in vivo experimental models, which are likely related to the expression of different virulence factors. Amastin is a surface glycoprotein abundantly expressed on the intracellular mammalian amastigote form of the parasite. In this study, we showed that a highly infective strain (G strain) of extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 43 publications
4
34
0
2
Order By: Relevance
“…Because G strain has been largely characterized as a low virulence strain [18], we speculated that members of the δ-amastins sub-family may constitute virulence factors that contributed to the infection capacity and parasite survival in the mammalian host. This hypothesis has been recently verified by experiments in which we over-expressed one δ-amastin gene in the G strain and showed that the transfected parasites have accelerated amastigote differentiation into trypomastigotes in in vitro infections as well as parasite dissemination in tissues after infection in mice [19]. It is also noteworthy that both β-amastins exhibited increased levels in epimastigotes of all strains analysed, indicating that this amastin isoform may be involved with parasite adaptation to the insect vector.…”
Section: Resultsmentioning
confidence: 54%
“…Because G strain has been largely characterized as a low virulence strain [18], we speculated that members of the δ-amastins sub-family may constitute virulence factors that contributed to the infection capacity and parasite survival in the mammalian host. This hypothesis has been recently verified by experiments in which we over-expressed one δ-amastin gene in the G strain and showed that the transfected parasites have accelerated amastigote differentiation into trypomastigotes in in vitro infections as well as parasite dissemination in tissues after infection in mice [19]. It is also noteworthy that both β-amastins exhibited increased levels in epimastigotes of all strains analysed, indicating that this amastin isoform may be involved with parasite adaptation to the insect vector.…”
Section: Resultsmentioning
confidence: 54%
“…Transfected G (Tc I, GFP) (Cruz et al , ) and CL (TcVI, DsRed) (Brener et al , ) parasite strains were cycled as epimastigotes in LIT medium or Vero cell culture monolayers as trypomastigotes, as previously described (Cruz et al , ). Trypanosoma expression construct (pTREX‐DsRm) containing DsRed fluorescent protein was prepared using standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Transfected G (Tc I, GFP) (Cruz et al, 2012) and CL (TcVI, DsRed) (Brener et al, 1963) parasite strains were cycled as epimastigotes in LIT medium or Vero cell culture monolayers as trypomastigotes, as previously described (Cruz et al, 2012).…”
Section: Parasitesmentioning
confidence: 99%
“…Cruz et al (2012) demonstrated that the treatment of HeLa cells with recombinant amastin, a surface glycoprotein abundant in amastigotes, reduced the infectivity of EA forms. Conversely, the ectopic T. cruzi expression of amastin accelerated differentiation of amastigotes into trypomastigotes.…”
Section: Eas Molecules Of Adhesion and Secretion: Invasion And Signalingmentioning
confidence: 99%